Resection of heterotopic ossification around the hip after trauma. Issue 6 (3rd June 2019) - de l'Escalopier, Nicolas; Salga, Marjorie; Gatin, Laure; Genêt, François; Denormandie, Philippe
Abstract : Traumatic neurological lesions may lead to development of heterotopic ossification. These cases are classified as 'neurogenic heterotopic ossifications' (NHOs). The associated neurological lesions can be caused by cranial trauma or spinal cord injury and may sometimes include a local trauma. NHOs that form around the hip joints are of particular interest because they often cause the patient to avoid the sitting position or the resumption of walking. Whilst NHO can involve the knee, shoulder and elbow joints, hip-involving NHOs are more numerous, and sometimes develop in close contact with vascular or neurological structures. Multi-disciplinary clinical examination is fundamental to evaluate patients for surgical intervention and to define the objectives of the surgery. The best investigation to define an NHO mass is a computerized tomography (CT) scan. Resection is performed to liberate a fused joint to provide functionality, and this need not be exhaustive if it is not necessary to increase the range of motion. While recurrence does occur post-surgery, a partial resection does not pose a greater risk of recurrence and there are no adjuvant treatments available to reduce this risk. The greatest risks associated with NHO surgical resection are infection and haematoma; these risks are very high and must be considered when evaluating patients for surgery. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180098